ChatGPT for the Future of Science Learning: A Systematic Literature Review - Yuliarman Saragih; Pradicta Nurhuda; Sudirman Sudirman; Gustina Indriati; Nugroho Susanto (Jurnal Penelitian Pendidikan IPA, 2023)
The rapid era of technological development has had a major impact on the world of education. At least the challenges faced by the education sector are related to the use of Chat GPT artificial intelligence in the science learning process. Through science education, students can engage in the impact of science in everyday life and the role of students in society. The provision of quality science education will have an impact on the development achievements of a country. for this reason, research was carried out. The purpose of the research is to explain ChatGPT for the Future of Science Learning. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines We must know and practice changes in education and learning patterns at all levels of education by describing the characteristics of learning that are currently needed. The results of this research show that in science learning there are several main domains on which the learning objectives using the science approach pattern are based on the advantages of this approach. GPT chat can be used to get answers to various problems and questions, providing precise and fast responses. GPT chat plays an important role in shaping the science learning system of the future. Many benefits have been found from GPT chat in science learning.